2003
DOI: 10.1210/jc.2002-021052
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ghrelin Levels Are Inversely Correlated with Body Mass Index, Age, and Insulin Concentrations in Normal Children and Are Markedly Increased in Prader-Willi Syndrome

Abstract: Ghrelin, an endogenous ligand of the GH secretagogue receptor, stimulates appetite and causes obesity in animal models and in humans when given in pharmacologic doses. Prader-Willi Syndrome (PWS) is a genetic obesity syndrome characterized by GH deficiency and the onset of a voracious appetite and obesity in childhood. We, therefore, hypothesized that ghrelin levels may play a role in the expression of obesity in this syndrome. We measured fasting serum ghrelin levels in 13 PWS children with an average age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
233
6
9

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(276 citation statements)
references
References 27 publications
28
233
6
9
Order By: Relevance
“…The present study confirms previous reports (DelParigi et al, 2002, Haqq et al, 2003, Goldstone et al, 2004and Tauber et al, 2004) that fasting and postprandial ghrelin levels are significantly higher in PWS subjects compared to obese and lean subjects. However, in contrast to previous reports , Goldstone et al, 2004, Goldstone et al, 2005and McLaughlin et al, 2004, our data suggest that the observed increase in ghrelin in PWS is not due to altered fat distribution or hypoinsulinemia because PWS and obese subjects were matched for total and central adiposity and showed similar insulin secretion and insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…The present study confirms previous reports (DelParigi et al, 2002, Haqq et al, 2003, Goldstone et al, 2004and Tauber et al, 2004) that fasting and postprandial ghrelin levels are significantly higher in PWS subjects compared to obese and lean subjects. However, in contrast to previous reports , Goldstone et al, 2004, Goldstone et al, 2005and McLaughlin et al, 2004, our data suggest that the observed increase in ghrelin in PWS is not due to altered fat distribution or hypoinsulinemia because PWS and obese subjects were matched for total and central adiposity and showed similar insulin secretion and insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to the imaging results, the blood plasma levels of glucose, insulin, ghrelin and PYY were found in accordance with the predictions: levels of all of the above were significantly different between the fasting and high-energy meal conditions. While ghrelin levels were elevated in comparison to controls in previously published literature, 35,[41][42][43] recent work has shown that even when ghrelin levels are reduced to a normal level, using somatostatin or a somatostatin agonist, there is no effect on appetite or food intake in individuals with PWS. 44,45 This suggests that the dysfunction in PWS is central in origin, rather than as a result of abnormalities in the periphery, at least in terms of the measures in this study.…”
Section: Discussionmentioning
confidence: 70%
“…A reduction in plasma ghrelin in the obese A y /a mouse is consistent with the low plasma ghrelin found in obese humans. [37][38][39] The reduction in Arc NPY mRNA expression in obese A y /a mice may contribute to their increased linear growth. Our observation is in contrast to a previous study of obese A y /a mice of a comparable age and body weight that used similar techniques.…”
Section: Discussionmentioning
confidence: 99%